Balloon inflation impression technique - Yahiya, Bazanth; Paul, Denis; C.Peedikayil, Faizal (Journal of Oral and Dental Sciences, 2017)
Background: Impression recording can become a challenging procedure in a patient with high arch palate and cases with altered palatal morphology.Method: A stock tray is modified with a hole in the center corresponding to the rubber tube diameter of a sphygmomanometer. Tube is inserted into the hole with a vinyl glove fastened to it with the help of rubber bands or cyanoacrylate. Minimal amount of additional polysilicon material is loaded on to the tray, and assembly is carried into patient’s mouth. Vinyl Gloves are inflated, and knob is locked. Tray is kept in a position till the material sets, and the whole assembly is removed with caution.Result: This innovative impression recording technique showed better recording of impression in cases with high palatal vault.Conclusion: This impression procedure is an alternative to the traditional impression recording procedure to yield better treatment results in patients with anatomical variations.
Keywords: Additional Polysilicon; Higharch Palate; Sphygmomanometer; Vinyl Glove